Polyurethane foams based on modified tung oil and reinforced with rice husk ash I: Synthesis and physical chemical characterization - Silva, Virginia Ribeiro da (2013)
A chemically modified tung oil was used as the main polyol component in the formulation of viscoelastic (low resilience) polyurethane foams. Rice Husk Ash (RHA), a residue from the rice process industry, was chosen to be incorporated as rigid filler in these materials because of its high silica content. Water was used as blowing agent in order to increase the green nature of the reinforced foams. Physico-chemical and thermal properties of the neat and reinforced foams were measured and analyzed. RHA addition leads to noticeable changes in several properties, mainly thermal conductivity, density and foam morphology, even at the low filler content used in this work. Although the thermal stability was almost unaffected by ash content, a stabilizing effect of the inorganic filler was identified, since the residual char was higher than predicted from theoretical calculations.